Psychological safety in elite swimming: fearful versus fearless coaching environments - Maughan, A. B.; Jowett, S. (International Sport Coaching Journal, 2025)
Psychological safety has become a popular concept within organisational settings and recently has become a topic of interest within sport. The purpose of this paper was to explore the notion of psychological safety and its impact on athletes` performance, as well as examine the role coaches played in creating psychologically safe environments. Semistructured interviews were conducted with five former female elite swimmers—all of whom had represented their country in Olympic Games and/or World Championships at least once. Obtained qualitative data were transcribed and analysed using reflexive thematic analysis. The analysis generated three main themes: (a) fearful coaching environment, (b) fearless coaching environment, and (c) team environment. All participants experienced both the presence and lack of psychological safety during their athletic careers. According to the participants, their coaches played a fundamental role in creating coaching environments that either invoked or suppressed fear. Swimming teams formed by peers also contributed to experiencing psychological safety (or lack of). This study highlights that an investigation of the content and functions of psychological safety within specific sport contexts can garner insightful knowledge that can have important theoretical and practical ramifications for coaches and coaching in sport.